PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER SATISFACTION PADA PRODUK TEH PT PERKEBUNAN TAMBI WONOSOBO - ABDULLAH ZAILANI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2015)
The objectives of this research was: (1) To determine the influence of Understanding Customer Expectations, Building Service Partnership, Empowering Employees, for the partial Customer Satisfaction at PT Plantation Tambi tea products in Wonosobo (2) To determine the influence of variables Understanding Customer expectation, Building Service Partnership, Total Quality Management, and Empowering Employees simultaneously to Customer Satisfaction in PT Plantation Tambi tea products in Wonosobo. (3) To determine the independent variables Understanding Customer Expectations, Building Service Partnership, Total Quality Management, and Empowering Employees are the most dominant of the Customer Satisfaction At PT Plantation Tambi tea products in Wonosobo. This research was conducted at the user / consumer of Black Tea Plantation Tambi PT Territory Wonosobo. Total sample of 100 respondents. The analysis tool used is multiple linear regression. The results showed that partially known that variable Understanding Customer Expectations and Building Service Partnership no significant effect on Customer Satisfaction at PT Plantation Tambi tea products. While Empowering Employees significant effect on Customer Satisfaction at PT Plantation Tambi tea products. From the test results simultaneously known that variables Relationship Marketing consisting of Understanding Customer Expectations, Building Service Partnership, Total Quality Management, and Empowering Employees jointly affect the Customer Satisfaction at PT Plantation Tambi tea products in Wonosobo. Of the partial test results show that the variable Total Quality Management proven effect partially dominant than the variable Understanding Customer Expectations, Building Services Partnership, and Empowering Employees.